Długoterminowa (nie)skuteczność algorytmu SuperMemo w szkolnej edukacji historycznej - Piotrowski, Mikołaj (Kultura-Społeczeństwo-Edukacja, 2024)
The subject of the article is the SuperMemo algorithm, which forms the basis of various applications that aid in memorization. It has been implemented in programs such as Anki or an application named after the algorithm itself – SuperMemo. An experimental study of its long-term effectiveness in school historical education was conducted among 59 students preparing for their final exams in history or participating in olympiads and attending above-average rated high schools and technical schools in Poland. The results indicate little interest in such a service, which is likely representative of other students less engaged in studying history.